Detection of Salmonella sp. in broiler chickens in closed houses using the polymerase chain reaction method - Larasati, Anissa Dhea; Sabdoningrum, Emy Koestanti; Nidom, Chairul Anwar; Hidanah, Sri; Rachmawati, Kadek; Puspitasari, Yulianna (Jurnal Agro Veteriner, 2025)
This study aimed to detect the presence of Salmonella sp. in broiler chickens raised in closed house systems using the Polymerase Chain Reaction (PCR) method. Liver and intestinal samples were collected from chickens showing clinical signs such as diarrhea, anorexia, and lethargy, along with pathological lesions observed during necropsy. Bacteriological identification involved isolation using selective media, Gram staining and biochemical tests. Two samples (3A and 3B) showed colony morphology and biochemical characteristics consistent with Salmonella sp. Confirmation using PCR targeting the invA gene (primers 139 and 141, expected amplicon size 284 bp) yielded negative results in both samples, while the positive control successfully amplified the target. The inconsistency between bacteriological and molecular results may be attributed to several factors: absence or mutation of the invA gene in the tested isolates, primer mismatch with local Salmonella strains, or inadequate DNA quality and concentration. These findings suggest that reliance on a single molecular marker may be insufficient for accurate detection and underscore the importance of optimizing PCR conditions. The study highlights the need for locally adapted primers and complementary diagnostic approaches to improve the reliability of Salmonella sp. detection in poultry, particularly in intensive production systems like closed house environments.